The principle of equality of economic opportunity in the regulatory frameworks underpinning European Union Member State income tax systems - Seniņa, Samanta (Riga Graduate School of Law, 2024)
This bachelor thesis examines the legislative framework of income tax systems in the European Union (EU), with a specific focus on their impact on economic inequality. Income tax rates and systems in the EU vary among Member States, reflecting distinct policy differences. The following thesis also examines the principle of equality in the legislative frameworks of EU Member States and evaluates the efficiency of these structures in addressing economic inequality. This thesis primarily consists of extensive literature research and a meticulous analysis of the legal mechanisms that govern income tax law and its characteristics in European Union Member States. The thesis seeks to assess the correlation between income tax legislation and economic inequality by studying empirical data from the last few decades and pertinent case studies. This thesis additionally examines legal barriers and other fundamental issues that ultimately cause economic inequality, providing valuable insights into the intricate interplay between legislation, taxes, and social fairness within the European Union. Ultimately, the thesis investigation seeks to assess the level of integration of the principle of economic equality into the income tax systems of EU Member States.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Tax law; progressive income tax; European Union; economic inequality